Kinematic and kinetic analyses of the vertical jump with and without header as performed by para-footballers with cerebral palsy - Reina, R.; Elvira, J. L. L.; Valverde, M.; Roldán, A.; Yanci, J. (Sports, 2019)
Vertical jump is a relevant variable in the classification of football for individuals with cerebral palsy. In this regard, the literature is limited. There are no studies assessing vertical jumping ability through kinematic methods and in more specific football game situations, such as jumps with a header. The goals of the present study were to assess how the modification of jumping conditions (without and with a header) might affect the kinematic and kinetic parameters of counter movement jumping, and whether the functional profiles of the players constrain their ability to jump vertically, both with and without a header. Thirteen male football players with cerebral palsy (27.7 ± 5.7 years old) and different functional profiles participated in this study. All the players performed ten counter movement jumps with arms swing, five headed a ball and five did not. The kinematic parameters were recorded with a 3D motion analysis system, and the kinetic parameters using a force platform. Significantly smaller angles of the hips (dg = 0.75-0.79; p < 0.01) and knees (dg = 1.04-1.15; p < 0.05), as well as greater ankle extension (dg = -0.71; p < 0.05), were observed during the eccentric phase of the jumps with a header. There were also asymmetries between legs in ankle extension during jumps with a header (dg = -1.06; p < 0.05), which could be an adjustment element for the precision of the jumps (i.e., header action). It should be mentioned that the jumping pattern could be partially affected by the functional profile of football players with cerebral palsy.